An improvement of H. Wang preconditioner for L-matrices - Nasabzadeh, Hamideh (International Journal of Applied Mathematical Research, 2016)
In this paper, we improve the preconditioner, that introduced by H. Wang et al [6]. The H. Wang preconditioner \(PR^n× n\) has only one non-zero, non-diagonal element in \(P_n1\) or \(P_1n\) , when \(a_1na_n1 e 0\) . But the new preconditioner has only one non-zero, non-diagonal element in Â \(P_ij\) or Â \(P_ji\) if \(a_ija_ji e 0\), so the H. Wang preconditioner is a spacial case of the new preconditioner for L-matrices. Also we present two models to construct a better \(I+S\) type preconditioner for the Â \(AOR\) iterative method. Convergence analysis are given, numerical results are presented which show the effectiveness of the new preconditioners.